Cloning of the cDNA for sea bream (Sparus aurata) parathyroid hormone-related protein - Flanagan, J. A. (2014)
This paper reports cloning of the cDNA for sea bream (Sparus aurata) parathyroid hormone-related protein (PTHrP). The gene codes for a 125-amino acid mature protein with a 35-residue prepeptide. The total gene sequence is 1.8 kb with approximately 75% noncoding. The N-terminus of the protein resembles mammalian and chicken PTHrP peptides with 12 of the first 21 amino acids identical and for which there is homology with mammalian parathyroid hormone. Toward the C-terminus, the nuclear transporter region between residues 79 and 93 in sea bream is 73% homologous to tetrapod PTHrP, and the RNA binding domain, 96–117, is 50% homologous, moreover starting with the conserved lysine and terminating with the lysine/arginine sequence. Sea bream PTHrP differs significantly from mammalian and chicken PTHrP, having a novel 16-amino acid segment between residues 38 and 54 and completely lacking the terminal domain associated in mammals with inhibition of bone matrix lysis. RT-PCR and in situ hybridization of sea bream tissues show that the gene is expressed widely and the results confirm observations of a PTHrP-like factor in sea bream detected with antisera to human PTHrP.